2016
DOI: 10.1093/mnras/stw397
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and oxygen abundance gradients in NGC 300 and M33 from optical recombination lines

Abstract: We present deep spectrophotometry of several H ii regions in the nearby low-mass spiral galaxies NGC 300 and M 33. The data have been taken with UVES and OSIRIS spectrographs attached to the 8 m VLT and 10.4 m GTC telescopes, respectively. We have derived precise values of the physical conditions for each object making use of several emission line-intensity ratios. In particular, we have obtained direct determinations of the electron temperature in all the observed objects. We detect pure recombination lines (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 94 publications
(135 reference statements)
6
58
2
Order By: Relevance
“…Fig. 10 reinforces the results obtained by Toribio San Cipriano et al (2016). They presented the first indication that the slopes of the C/H -and to a lesser extent C/O -gradients show a clear correlation with the M V of the galaxies.…”
Section: The Spatial Distribution Of O and C Abundances In The Mcssupporting
confidence: 89%
See 3 more Smart Citations
“…Fig. 10 reinforces the results obtained by Toribio San Cipriano et al (2016). They presented the first indication that the slopes of the C/H -and to a lesser extent C/O -gradients show a clear correlation with the M V of the galaxies.…”
Section: The Spatial Distribution Of O and C Abundances In The Mcssupporting
confidence: 89%
“…The ADFs obtained in the SMC are at the higher end of these typical values. Esteban et al (2014) and Toribio San Cipriano et al (2016) have found ADFs of about 0.3-0.4 dex in the case of star-forming dwarf galaxies and H ii regions in the spiral galaxy NGC 300, respectively. Tsamis et al (2003) determined the ADF(O 2+ ) for 30 Doradus and N11B in the LMC and for N66 in the SMC.…”
Section: Adf(o 2+mentioning
confidence: 98%
See 2 more Smart Citations
“…We supplement this sample with recent observations of extragalactic H ii regions from Croxall et al (2016) and Toribio San Cipriano et al (2016), bringing the total sample size to 1052. While all of the H ii regions in this sample have measurements of at least one auroral line, some of these auroral-line measurements have low S/N or are otherwise unreliable.…”
Section: Abundances and Line Emission Of H II Regionsmentioning
confidence: 99%